FAT-GEMs: (field assisted) transparent gaseous-electroluminescence multipliers - Leardini, S.; Saá-Hernández, A.; Kuźniak, M.; González-Díaz, D.; Azevedo, C. D. R.; Lucas, F.; Amedo, P.; Cortez, A. F. V.; Fernández-Posada, D.; Mehl, B.; Nieradka, G.; de Oliveira, R.; et al. (Frontiers in Detector Science and Technology, 2024)
The idea of implementing electroluminescence-based amplification through transparent multi-hole structures (FAT-GEMs) has been entertained for some time. Arguably, for such a technology to be attractive it should perform at least at a level comparable to conventional alternatives based on wires or meshes. We present now a detailed calorimetric study carried out for 5.9 keV X-rays in xenon, for pressures ranging from 2 to 10 bar, resorting to different geometries, production and post-processing techniques. At a reference voltage 5 times above the electroluminescence threshold (𝐸𝐸 𝐿,𝑡 ℎ ∼ 0.7 kV/cm/bar), the number of photoelectrons measured for the best structure was found to be just 18% below that obtained for a double-mesh with the same thickness and at the same distance. The energy resolution stayed within 10% (relative) of the double-mesh value. An innovative characteristic of the structure is that vacuum ultraviolet (VUV) transparency of the polymethyl methacrylate (PMMA) substrate was achieved, effectively, through tetraphenylbutadiene (TPB) coating of the electroluminescence channels combined with indium tin oxide (ITO) coating of the electrodes. This resulted in a ×2.25-increased optical yield (compared to the bare structure), that was found to be in good agreement with simulations if assuming a TPB wavelength-shifting-efficiency at the level of WLSE=0.74-1.28, compatible with expected values. This result, combined with the stability demonstrated for the TPB coating under electric field (over 20 h of continuous operation), shows great potential to revolutionize electroluminescence-based instrumentation.